Development and regulation of chloride homeostasis in the central nervous system - Watanabe, Miho; Fukuda, Atsuo (Frontiers in Cellular Neuroscience, 2015)
GABA (γ-aminobutyric acid) is the main inhibitory neurotransmitter of the mature central nervous system. The developmental switch of GABAergic transmission from excitation to inhibition is induced by changes in Cl- gradients, which are generated by cation-Cl- co-transporters. An accumulation of Cl- by the Na+-K+-2Cl- co-transporter (NKCC1) increases the intracellular Cl- concentration ([Cl-]i) such that GABA depolarizes neuronal precursors and immature neurons. The subsequent ontogenetic switch, i.e., upregulation of the Cl--extruder KCC2, which is a neuron-specific K+-Cl- co-transporter, with or without downregulation of NKCC1, results in low [Cl-]i levels and the hyperpolarizing action of GABA in mature neurons. Development of Cl- homeostasis depends on developmental changes in NKCC1 and KCC2 expression. Generally, developmental shifts (decreases) in [Cl-]i parallel the maturation of the nervous system, e.g., early in the spinal cord, hypothalamus and thalamus, followed by the limbic system, and last in the neocortex. There are several regulators of KCC2 and/or NKCC1 expression, including BDNF, insulin-like growth factor, and CFTR. Therefore, regionally different expression of these regulators may also contribute to the regional developmental shifts of Cl- homeostasis. KCC2 and NKCC1 functions are also regulated by phosphorylation by enzymes such as PKC, Src-family tyrosine kinases, and WNK1-4 and their downstream effectors SPAK-OSR1. In addition, activation of these kinases is modulated by humoral factors such as estrogen and taurine. Because these transporters use the electrochemical driving force of Na+ and K+ ions, topographical interaction with the Na+-K+ ATPase and its modulators such as creatine kinase should modulate functions of Cl- transporters. Therefore, regional developmental regulation of these regulators and modulators of Cl- transporters may also play a pivotal role in the development of Cl- homeostasis.